Rapid adenovirus typing by immunoelectron microscopy - Luton, P. (1973)
A rapid method of typing adenoviruses by immunoelectron microscopy is discribed. This emphasizes the value of an electron microscope in diagnostic virology, especially when a rapid result is required in epidemiology.